Complete mesocolic resection and extended lymphadenectomy for colon cancer: a systematic review. (August 2014) - Killeen, S.; Mannion, M.; Devaney, A.; Winter, D. C.
Abstract Aim Complete mesocolic excision (CME) and extended lympha‐denectomy (EL) have been proposed as safe procedures for improving colon cancer survival outcomes. The aim of this study was to evaluate the evidence regarding oncological outcomes, morbidity and mortality after such techniques for colon cancer. Method A systematic review of the literature was conducted to evaluate evidence regarding oncological outcomes, morbidity and mortality after CME or EL. Three major databases (PubMed, MEDLINE and the Cochrane Library) were searched. The review included original articles reporting outcomes after CME or EL from January 1950 to July 2012. Results Twenty‐one, predominately retrospective, studies involving 5246 patients (mean age 68.2 years, 56.5% men) were included. Reporting of outcomes was inconsistent. Median follow up was 60 months. The operative mortality rate was 3.2% and the cumulative morbidity rate was 21.5%. The weighted mean local recurrence rate and the 5‐year overall and disease‐free survival rates were 4.5%, 58.1% and 77.4%, respectively. Conclusion The available data for CME and EL have numerous fundamental limitations that prohibit adoption. Contemporary controlled studies are required before universal recommendation.